ANALYSIS OF STUDENT ERROR IN SOLVING THE FUNDAMENTAL METHOD OF COUNTING BASED ON NEWMAN’S THEORY - Rayinda Aseti Prafianti; Rachman Arief (MATEMATIKA DAN PEMBELAJARAN, 2022)
The purpose of this study was to find out: (1) what types of errors were made by students in solving questions on the fundamental method of counting, (2) what factors caused students to make mistakes in solving questions on the fundamental method of counting. This study used descriptive qualitative method. The subject of this research is the first semester of Informatics Engineering students. Data collection using test and interview methods. Data analysis techniques include the stages of data reduction, data presentation, and verification and drawing conclusions. In this study, student errors were analyzed based on Newman's five error indicators, (a) errors in reading questions, (b) errors in understanding questions, (c) errors in process transformation, (d) errors in process skills, and (e) errors in write down the final answer. Based on the results of the analysis, it was found that the types of errors made by Informatics Engineering students in solving the questions of the fundamental method of counting were three, namely (1) errors in receiving information including errors in determining what was asked the cause was not being careful in reading the questions, (2) errors related concepts include: (a) errors in using permutation and combination formulas. The reason is that students cannot understand the meaning of the problem, when to use permutations and when to use combinations. And (3) errors in counting, the cause is because students are not careful.